Сучасні тенденції формування бюджету маркетингу на українських підприємствах - Соломянюк, Наталія Миколаївна (My University, 2013)
У статті розглянуто функції маркетингу вітчизняних підприємств, на основі яких формуються дискреційні статті витрат, поєднаних у бюджет маркетингу. Запропоновано схему послідовності розгортання загального бюджету маркетингу на його складові залежно від маркетингових цілей у системі діяльності підприємства. Здійснено аналіз структурних витрат українських підприємств на маркетинг у сучасних умовах господарювання. Проаналізовано тенденції перерозподілу витрат на маркетинг підприємствами залежно від обсягів річної виручки реалізації. In the article the functions of marketing at Ukrainian enterprises are considered. Such functions form the discretionary items of expenses combined in the budget of marketing. Introduction. Complexity and controversy of marketing budgets planning at Ukrainian enterprises in modern economic conditions require study of possibilities for discretionary marketing expenses redistribution. Purpose. To form a methodological approach to classification of main marketing functions of domestic enterprises in order to marketing complex and discretionary expenses of marketing budget. Results. The author proposes the model of marketing budget forming which aims to realize all strategic marketing functions at the enterprise. She states the importance to correlate budgeting with the conditions of external environment. She characterizes these conditions in Ukraine mentioning total Ukrainian advertisement market growth to 9%. In 2012, for advertisement production and placement $1,75 billions were spent. This is mainly because of global brands presence at Ukrainian market and globalization tendencies strengthening. The tendencies of enterprises’ marketing budgets structures and changes in them were also analyzed by the author. Conclusions. The modern tendencies of marketing budgets forming in Ukraine were strongly affected by such economic and political processes taking place in Ukraine, as: financial crisis combined with state economic policy, swift changes at advertising market (decrease of demand for some kinds of advertisement, cut of advertisement budgets); marketing specialists layoff. The size of Ukrainian enterprises’ marketing budget depends on the product which will be promoted. Moreover, there is always a volume of market capacity which is a border for effective marketing expenses at the certain market. Therefore it is important, concludes the author, to use new marketing technologies and to redistribute marketing expenses for prospective directions on time.
Keywords: бюджет маркетинга; marketing budget; функції маркетингу; marketing functions; витрати на маркетинг; marketing expenses; кафедра маркетингу